Late MRD response determines relapse risk overall and in subsets of childhood T-cell ALL: results of the AIEOP-BFM-ALL 2000 study - Schrappe, Martin; Valsecchi, Maria Grazia; Bartram, Claus R.; Schrauder, André; Panzer-Grümayer, Renate; Möricke, Anja; Parasole, Rosanna; Zimmermann, Martin; Dworzak, Michael; Buldini, Barbara; Reiter, Alfred; Basso, Giuseppe; et al. (Blood, 2011)
The prognostic value of MRD in large series of childhood T-ALL has not yet been established. Trial AIEOP-BFM-ALL 2000 introduced standardized quantitative assessment of MRD for stratification, based on immunoglobulin and TCR gene rearrangements as polymerase chain reaction targets: Patients were considered MRD standard risk (MRD-SR) if MRD was negative at day 33 (time point 1 [TP1]) and day 78 (TP2), analyzed by at least 2 sensitive markers; MRD intermediate risk (MRD-IR) if positive either at day 33 or 78 and < 10−3 at day 78; and MRD high risk (MRD-HR) if ≥ 10−3 at day 78. A total of 464 patients with T-ALL were stratified by MRD: 16% of them were MRD-SR, 63% MRD-IR, and 21% MRD-HR. Their 7-year event-free-survival (SE) was 91.1% (3.5%), 80.6% (2.3%), and 49.8% (5.1%) (P < .001), respectively. Negativity of MRD at TP1 was the most favorable prognostic factor. An excellent outcome was also obtained in 32% of patients turning MRD negative only at TP2, indicating that early (TP1) MRD levels were irrelevant if MRD at TP2 was negative (48% of all patients). MRD ≥ 10−3 at TP2 constitutes the most important predictive factor for relapse in childhood T-ALL. The study is registered at http://www.clinicaltrials.gov; “Combination Chemotherapy Based on Risk of Relapse in Treating Young Patients With Acute Lymphoblastic Leukemia,” protocol identification #NCT00430118 for BFM and #NCT00613457 for AIEOP.
Gesehen am 26.10.2022